Usability of gaming environments in cybersport - Sergeev, S.; Kaklauskas, A. (MATEC Web of Conferences, 2018)
The article is devoted to the issues of engineering and psychological evaluation of gaming interfaces and environments for eSports. The typical program interface of group computer games is analyzed from the point of view of their user properties (usability). The functions and structure of the game interface are discussed. Definitions are given and the main usability functions are considered as an application to the gaming systems used in eSports. The basic requirements for user properties are formulated, and definitions of usability are given in accordance with the requirements of the International Organization for Standardization (ISO). The basic concepts of usability testing are given.